Development of Character Education (Analysis of Ibn Miskawaih's Thought) - Darmawati Darmawati; Ambo Dalle; Fikri Haekal Amdar; Abdul Aziz Bin Mustamin (Institut Agama Islam Negeri Bengkulu, 2020)
Ibn Miskawaih was a great Islamic philosopher, most of his knowledge was obtained through reading. Thus Ibn Miskawaih can be called a successful self-taught. Of his many works, Ibn Miskawaih's thoughts were heavily influenced by Greek philosophy, Persian civilization, the teachings of Islamic law and personal experience. Even though none of them were found that specifically discussed character education, some of his works were considered to have a lot to do with education. Ibn Miskawaih himself acknowledged that the essence and function of education is to shape the personality of the human being so that a man who has an evil and a commendable character is formed.